Design and Construction of the Action Role-Playing Game: Supply Odyssey Using the Game Development Life Cycle Method - Dewanata, Enggaling Aji; Willis, Tito Bisma May (LPPM Telkom University Surabaya, 2025)
The rapid development of the global gaming industry has made games not only serve as entertainment but also as a medium for learning, social interaction, and game-based entrepreneurship. One of the most widely favoured genres is the Action Role-Playing Game (Action RPG), which combines action elements with RPG mechanics. This research aims to design and develop a 2D video game titled “Supply Odyssey” in the Action RPG genre using the Godot Engine as the primary development platform. Godot was selected due to its open-source nature, free licensing, and strong support for both indie and professional developers. The research employs the Game Development Life Cycle (GDLC) methodology, incorporating the Line of Sight (LOS) technique to model enemy (NPC) behaviour. The implementation of LOS is expected to increase combat realism and provide greater tactical depth in real-time encounters by enabling players to strategize according to enemy visibility ranges, select optimal positions, and engage in more dynamic interactions. Supporting data were collected through observations on game platforms and developer and gamer community forums to identify relevant trends, preferred game concepts, and engaging gameplay patterns. The results of this research are expected to produce an Action RPG game that not only offers entertainment but also contributes to the development of Godot-based games and serves as a reference for applying GDLC and LOS methods in similar game development projects.